Agama di Era Post-Truth: Antara Populisme Agama dan Banalitas Sosial - Djaya, Sulaiman (Dakwah: Jurnal Kajian Dakwah dan Kemasyarakatan, 2024)
This article is an attempt to reflect on the dilemma of the post truth era and information technology for the existence of health and spiritual piety of mankind, and the phenomenon of theological bias and religious extremity in this era. Humans live in a post-truth era, many call it a post-religious era, but this claim is not proven considering that religious populism is currently happening. In this era, information technology and social media with various platforms such as Facebook, Instagram, Tiktok, YouTube and others have become media and instruments that allow anyone to connect with each other at the same time. Geographical and national boundaries are melting and disappearing. This research uses a social-media approach. This research found that users of social media and information technology are vulnerable to becoming 'consumers of falsehoods' and hoaxes to propaganda from secular interests that hijack religious claims, such as hate propaganda. Information technology and social media that are too massive and abundant have actually caused many people to lose their attention span, weaken their memory, decrease their critical and analytical capacity and become addicted to things that are actually banal and instant. On the other hand, the public is led to favor materialist and secular trends and become active participants in a narcissistic-egoistic culture. Not to mention that information technology users become subjects who are indifferent to each other even when they are together when their focus and attention is more focused on their devices.